Obtenção, caracterização e aplicação de ovo de codorna em pó na produção de bolo pão de ló - Moreira, Camila Alves (2021)
Quail egg is a very nutritive food and still little explored by the food industry. Despite the rising in Brazilian production, the consumption of quail eggs is still significantly lower than chicken eggs. The drying of quail eggs can be an alternative to stimulate its production and consumption, given the greater transporting, storing and applying viability of powdered egg as an ingredient. This work consists of obtaining powdered quail egg by different drying methods, in addition to the characterization and application of the powders in the production of sponge cake. Conventional and foam-mat freeze-drying, and conventional (70 ºC for 5,5 hours) and foam-mat (70 ºC for 3,5 hours) oven drying with forced air circulation were used. The powders obtained were characterized as to color, moisture, water activity, bulk density, hygroscopicity, morphological and rehydration properties. Subsequently, the powdered eggs were rehydrated and analyzed as to color, pH and functional properties (gelling, foaming and emulsifying) and used as ingredients in sponge cakes production. The doughs were evaluated for moisture, specific gravity and viscosity, while the cakes were evaluated for weight, volume, color, texture and structure. The results showed greater applicability of the conventional freeze-drying egg (L-LIOF) compared to the other powders, owing to its physicochemical properties and good rehydration capacity, as well as its good performance in the sponge cake production. Foam- mat drying proved to be compensatory just for eggs produced by oven drying, as it optimized the rehydration capacity and foaming capacity, for example, promoting better cake characteristics, but with significantly lower performance compared to freeze-dried eggs. The foam-mat freeze-dried egg (E-LIOF) resulted in harder and less bulky cakes than cakes produced with L-LIOF egg, especially due to the lower foaming capacity. Although the pasteurized liquid egg has resulted in more desirable properties to the cakes, such as greater softness and volume, the L-LIOF egg also presented potential for the sponge cake production.